Pregnancy after the age of 35 as a pregnancy of high obstetric risk – the demand for education - Stobnicka, Dominika; Iwanowicz-Palus, Grażyna Jolanta; Korżyńska-Piętas, Magdalena; Dziaduszek, Katarzyna; Świst, Dorota (Journal of Education, Health and Sport, 2018)
Abstract The age is the basic factor influencing the woman’s fertility. The older woman is, the biological fertility is reduced. A woman reaches the maximum fertility at the age of 20-25 years, after which fertility gradually decreases, until the age of 35, when it drastically decreases. Late motherhood is associated with an increased risk of complications for woman and developing fetus’s health. Pregnancy after the age of 35 is considered a high-risk pregnancy since the possibility of the development of abnormalities in the functioning of the woman’s body and the course of pregnancy and childbirth. The phenomenon of postponing motherhood for a time when a woman acquires a good education and a stable financial situation requires undertaking educational and information activities about the biological, psychological and social consequences of late motherhood. It is definitely better to plan maternity at the most optimal age to minimize the risk of pregnancy and health of the child complications.